USING GOOGLE SITE-BASED LEARNING MEDIA FOR ENHANCING STUDENTS' INTERESTS IN ENTREPRENEURIAL LEARNING - Eli Yusnita; Sri Kartikowati; Hendripedes Hendripedes (International Journal of Educational Best Practices, 2023)
This study aims to ascertain the efficacy of employing Google site-based instructional materials in enhancing the students' interest in entrepreneurial education at the school under investigation. The research cohort comprised all twelfth-grade students of the school under investigation, with a sample of 30 students specifically from grade XII TKJ 2 at the school under investigation. Data for this research endeavor were gathered through the utilization of observation sheets and questionnaires measuring students' interest in learning. Analytical techniques deployed in this investigation encompassed descriptive analysis, prerequisite assessments, n-gain evaluations, and hypothesis testing. The findings reveal that the utilization of Google site-based learning resources effectively augmented students' interest in entrepreneurial education at the school under investigation. The hypothesis testing analysis, employing the Paired Sample t-test, indicated a t-test result with a two-tailed significance value (Sig.) of 0.000, which is less than the predetermined significance level of 0.05 (0.000 < 0.05). Consequently, the null hypothesis (H0) is rejected in favor of the alternative hypothesis (Ha). This outcome implies a noteworthy distinction in students' interest in learning when employing Google site-based instructional materials compared to students who do not utilize such resources at the school under investigation. In conclusion, the study demonstrates that Google site-based learning materials effectively heightened students' interest in entrepreneurial education at the school under investigation.